THE IMPACT OF FINANCIAL REPORTING FINANCIAL OPACITY ON CORPORATE INVESTMENT EFFICIENCY: EVIDENCE FROM IRAQ - Ammar Taha Yassin (Scholars Digest Publishing, 2024)
The main objective is to study and test the effect of opacity of financial reports on the investment efficiency according to the characteristics of companies for private banks listed on the Iraq Stock Exchange. Two conditions determined the research sample, the first is the data availability necessary to measure the research variables. The second is the continued disclosure of their data without interruption during the study period, and the research sample included the financial statements of ten banks for eight years (2016 to 2023), so views were eighty (bank / year). The analysis method of the informational content of the published financial reports has been adopted based on the descriptive analytical approach. The statistical program (SPSS Ver.22) has been used for the purpose of analyzing data, extracting results and testing research hypotheses. The main hypothesis was accepted. Also, the opacity of financial reports negatively affects the efficiency of investment and that some of the characteristics of the company affect positively (company size) and others (negatively) within the impact equation, that producing high quality financial reports (free from opacity) reduce the risks to investors and better identify investment opportunities. The research recommended the need for the Iraqi Securities Commission to play the supervisory role by obliging banks to disclose the necessary to increase the transparency of reports in a way that helps investors improve investment decisions. In addition, academics and researchers are advised to more examine the opacity of financial reports in the Iraqi business environment and on different economic sectors.
Keywords: financial opacity of financial reporting, investment efficiency , company characteristics, banking sector.